Etiology and Morphogenesis of Congenital Heart Disease: From Gene Function and Cellular Interaction to Morphology - Nakanishi, Toshio; Markwald, Roger R.; Baldwin, H.Scott; Keller, Bradley B.; Srivastava, Deepak; Yamagishi, Hiroyuki; Nakanishi, Toshio; Markwald, Roger R.; Baldwin, H.Scott; Keller, Bradley B.; Srivastava, Deepak; Yamagishi, Hiroyuki (Cham Springer Nature, 2016)
Cardiology; Pediatrics
English
Keywords: Medical profession; Cardiology; Pediatrics